Dehydroepiandrosterone and metyrapone partially restore the adaptive humoral and cellular immune response in endotoxin immunosuppressed mice - Rearte, Barbara (2013)
Prior exposure to endotoxins renders the host temporarily refractory to subsequent endotoxin challenge (endotoxin tolerance). Clinically, this state has also been pointed out as the initial cause of the non-specific humoral and cellular immunosuppression described in these patients. We recently demonstrated the restoration of immune response with mifepristone (RU486), a receptor antagonist of glucocorticoids. Here we report the treatment with other modulators of glucocorticoids, i.e. dehydroepiandrosterone (DHEA), a hormone with anti-glucocorticoid properties, or metyrapone (MET) an inhibitor of corticosterone synthesis. These drugs were able to partially, but significantly, restore the humoral immune response in immunosuppressed mice. A significant recovery of proliferative responsiveness was also observed when splenocytes were obtained from DHEA- or MET-treated immunosuppressed mice. In addition, these treatments restored the hypersensitivity response in immunosuppressed mice. Finally, although neither DHEA nor MET improved the reduced CD4 lymphocyte count in spleen from immunosuppressed mice, both treatments promoted spleen architecture reorganization, partially restoring the distinct cellular components and their localization in the spleen. The results from this study indicate that DHEA and MET could play an important role in the restoration of both adaptive humoral and cellular immune response in LPS-immunosuppressed mice, reinforcing the concept of a central involvement of endogenous glucocorticoids on this phenomenon.